1979
DOI: 10.1136/gut.20.9.750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-glucosidehydrolase inhibition and intestinal absorption of sucrose, water, and sodium in man.

Abstract: SUMMARY The effect of a new complex oligosaccharide exhibiting potent inhibitory action on ax-glucoside hydrolases on intestinal absorption of sucrose in man was tested by constant in vivo perfusion of the jejunum. At concentrations of 4-65 or 155 x 10-6M the ac-glucosidehydrolase inhibitor (a-GHI) markedly inhibited absorption of glucose from sucrose and absorption of sodium and water. Oral administration of the a-GHI resulted as well in depression of solute, sodium, and water absorption. This new compound ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…This effect could be related to an increase in total fecal bile acid excretion by about 70% [unpublished data]. It is conceiv able that bile acid absorption was affected by a net secretion of water and electrolytes in the small intestine which occurs in highly efficient disaccharidase inhibition [23]. Cho lesterol absorption also could have been di minished; but since acarbose was less effec tive in lowering serum cholesterol in the present experiment than in the initial study despite a lower intake of dietary cholesterol, it is likely that the observed changes of bile acid output were more important than a pos sible decrease of cholesterol absorption.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be related to an increase in total fecal bile acid excretion by about 70% [unpublished data]. It is conceiv able that bile acid absorption was affected by a net secretion of water and electrolytes in the small intestine which occurs in highly efficient disaccharidase inhibition [23]. Cho lesterol absorption also could have been di minished; but since acarbose was less effec tive in lowering serum cholesterol in the present experiment than in the initial study despite a lower intake of dietary cholesterol, it is likely that the observed changes of bile acid output were more important than a pos sible decrease of cholesterol absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Acarbose, an alpha-glucosidase inhibitor (αGI), improved postprandial hyperglycemia and reduced CAD incidence in patients with impaired glucose tolerance 12 and type 2 diabetes 13 . Among the oral antidiabetics, αGIs and glinides directly suppress postprandial plasma glucose (PG) levels by delaying intestinal absorption of glucose 14 and producing immediate insulin secretion 15 , respectively. We and other researchers reported that incretin-related drugs such as glucagon-like peptide-1 (GLP-1) receptor agonists 16 and dipeptidyl peptidase-4 (DPP-4) inhibitors 17,18 also improve postprandial hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Αυτός ο μηχανι σμός ο οποίος φαίνεται να λειτουργεί μόνον όταν χορη γείται πλήρες γεύμα, είναι δυνατόν.να αποτελεί έναν επιπλέον τρόπο, εκτός από την αναστολή των εντερικών δισακχαριδασών μ ε TC v οποίον η Ακαρβόζη επιμηκύνει έμμεσα την απορρόφηση των υδατανθράκων. (Caspary, 1978, Jenkins et al 1981, Caspary et al 1982.…”
unclassified